(untitled) - Elizabeth Eisner Reding; Elizabeth Eisner Reding (Boston, MA, 2006)
This new title offers comprehensive step-by-step instructions and in-depth explanations of the "how" and "why" behind the skills of Adobe Photoshop, CS2. Students will easily master each feature as they work through a wealth of information, including end-of-chapter learning projects and reviews and step-by-step tutorials. The full-color interior and user-friendly design create the ideal book for learning the latest features of this popular design application
Keywords: Adobe Photoshop; Photography--Digital techniques; Computer graphics